Financial Literacy, Financial Behaviour and Financial planning:-Implication for financial wellbeing of professionals - D, Arpana. (International Journal of Psychosocial Rehabilitation, 2020)
Indians are facing major problems such as low return on investment due to low financial literacy, debt trap, insufficient retirement fund and under insurance due to low financial literacy. Indian economy has witnessed a number of structural and fundamental changes in the financial markets. Over the past few decades, the study of how individuals make their financial decisions has become important to researchers, personal financial planners, investment counselors and policy makers especially considering the new changes that have increased the economic landscape complex. The development and advancement of the Indian economy and the extension of Financial markets through progression, privatization and globalization have given a path to a plenty of money related items either as a venture elective or a credit one. The survey has revealed that people in India do not plan for long-term future and keep themselves away from investing in the long-term instruments though they save for long-term goals such as emergencies, education and old age. Financial planning is also affected by external factors like social and economic factors and also individualistic factors like financial awareness, financial literacy, saving habits, risk taking ability etc. Hence it is important to understand the practices followed by Indians about financial planning, this article reviews the effect of financial behaviours in ways that enhance financial capability. Hence an attempt is made to analyse the effect of financial behaviour on financial planning and wellbeing of professionals.